Mercurial > hg > Members > kono > Proof > galois
changeset 266:e6f9eb2bfc78
...
author | Shinji KONO <kono@ie.u-ryukyu.ac.jp> |
---|---|
date | Tue, 31 May 2022 11:18:05 +0900 |
parents | 1dbe1f357569 |
children | 864afb582fc7 |
files | src/Fundamental.agda |
diffstat | 1 files changed, 18 insertions(+), 5 deletions(-) [+] |
line wrap: on
line diff
--- a/src/Fundamental.agda Tue May 31 09:49:12 2022 +0900 +++ b/src/Fundamental.agda Tue May 31 11:18:05 2022 +0900 @@ -59,6 +59,7 @@ base {G} {K} x = base1 (x ε) where -- with x ε won't work why? open Group G + -- Na ∙ Nb = Nab mul : {G : Group c l} {K : NormalSubGroup G} → (x y : (g : Group.Carrier G ) → Coset G K g ) → (g : Group.Carrier G ) → Coset G K g mul {G} {K} x y g = φ (base x ∙ base y) g where open Group G @@ -99,13 +100,25 @@ open Group G hiding (refl ; sym ; trans ) open EqReasoning (Algebra.Group.setoid G) open IsGroupHomomorphism (s-homo K ) - mbase : {x y : COSET G K} → base (mul x y) ≈ sub K (base x ∙ base y) + idem-base : {x : COSET G K} → sub K (sub K (base x)) ≈ sub K (base x ) + idem-base {x} = ib01 (x ε) where + ib01 : {a : Carrier } → (t : Coset G K a ) → sub K (sub K (base1 t)) ≈ sub K (base1 t ) + ib01 {y} (coset a b) = begin + sub K (sub K (base1 {G} {K} (coset a b))) ≈⟨ {!!} ⟩ + sub K (sub K (a ⁻¹ ∙ b)) ≈⟨ {!!} ⟩ + sub K (a ⁻¹ ∙ b) ≈⟨ {!!} ⟩ + sub K (base1 {G} {K} (coset a b)) ∎ + ib01 (cscong x t) = ib01 t + mbase : {x y : COSET G K} → sub K (base (mul x y)) ≈ sub K (base x ∙ base y) mbase {x} {y} = mbase1 (x ε) (y ε) where - mbase1 : {a b : Carrier } → Coset G K a → Coset G K b → base (mul x y) ≈ sub K (base x ∙ base y) + mbase1 : {a b : Carrier } → Coset G K a → Coset G K b → sub K (base (mul x y)) ≈ sub K (base x ∙ base y) mbase1 (coset a b) (coset a₁ b₁) = begin - (ε ∙ sub K (base1 (x ε) ∙ base1 (y ε)) ⁻¹) ⁻¹ ∙ (base1 (x ε) ∙ base1 (y ε)) ≈⟨ {!!} ⟩ - (sub K (base1 (x ε) ∙ base1 (y ε)) ⁻¹) ⁻¹ ∙ (base1 (x ε) ∙ base1 (y ε)) ≈⟨ {!!} ⟩ - (sub K (base1 (x ε) ∙ base1 (y ε))) ∙ (base1 (x ε) ∙ base1 (y ε)) ≈⟨ {!!} ⟩ + sub K ((ε ∙ sub K (base1 (x ε) ∙ base1 (y ε)) ⁻¹) ⁻¹ ∙ (base1 (x ε) ∙ base1 (y ε))) ≈⟨ {!!} ⟩ + sub K ((sub K (base1 (x ε) ∙ base1 (y ε)) ⁻¹) ⁻¹ ∙ (base1 (x ε) ∙ base1 (y ε))) ≈⟨ {!!} ⟩ + sub K ((sub K (base1 (x ε) ∙ base1 (y ε))) ∙ (base1 (x ε) ∙ base1 (y ε))) ≈⟨ {!!} ⟩ + sub K (sub K (base1 (x ε)) ∙ sub K (base1 (y ε)) ∙ (base1 (x ε) ∙ base1 (y ε))) ≈⟨ {!!} ⟩ + sub K (sub K (base1 (x ε)) ∙ base1 (x ε) ∙ sub K (base1 (y ε)) ∙ base1 (y ε)) ≈⟨ {!!} ⟩ + sub K (base1 (x ε)) ∙ sub K (base1 (y ε)) ≈⟨ {!!} ⟩ sub K (base1 (x ε) ∙ base1 (y ε)) ∎ mbase1 (coset a b) (cscong x t) = mbase1 (coset a b) t mbase1 (cscong eq s) (coset a b) = mbase1 s (coset a b)